Zgodnjesrednjeveški obredni prostor na najdišču Spodnje Škovce Early Medieval Sacral Area at the Site of Spodnje Škovce - Žorž, Alja (Studia mythologica Slavica, 2009)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The study represented in this contribution has been devoted to the remains of an Early Medieval sacral place discovered in last year excavations at the site of Spodnje Škovce. Several structures, such as double burial, a hearth with uncommon inventory, a small pit with clay daub and animal bones, and a shallow pit with schist stones, have shown ritual characteristics. With the use of interdisciplinary and integral approach to the inventory of the pits and their location, we have been able to improve our knowledge of Slav burial practices, as well as of their organization and ideological system.